Recombination Monophosphoryl Lipid A-Derived Vacosome for the Development of Preventive Cancer Vaccines - Cheng RY; Fontana F; Xiao JY; Liu ZH; Figueiredo P; Shahbazi MA; Wang SQ; Jin J; Torrieri G; Hirvonen JT; Zhang HB; Chen TT; et al. (American Chemical Society, 2022)
Recently, there has been an increasing interest for utilizing the host immune system to fight against cancer. Moreover, cancer vaccines, which can stimulate the host immune system to respond to cancer in the long term, are being investigated as a promising approach to induce tumor-specific immunity. In this work, we prepared an effective cancer vaccine (denoted as vacosome) by reconstructing the cancer cell membrane, monophosphoryl lipid A as a toll-like receptor 4 agonist, and egg phosphatidylcholine. The vacosome triggered and enhanced bone marrow dendritic cell maturation as well as stimulated the antitumor response against breast cancer 4T1 cells in vitro. Furthermore, an immune memory was established in BALB/c mice after three-time preimmunization with the vacosome. After that, the immunized mice showed inhibited tumor growth and prolonged survival period (longer than 50 days). Overall, our results demonstrate that the vacosome can be a potential candidate for clinical translation as a cancer vaccine.